1996
DOI: 10.1007/s002030050376
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonates: novel electron acceptors in anaerobic respiration

Abstract: The enrichment and isolation in pure culture of a bacterium, identified as a strain of Desulfovibrio, able to release and reduce the sulfur of isethionate (2-hydroxyethanesulfonate) and other sulfonates to support anaerobic respiratory growth, is described. The sulfonate moiety was the source of sulfur that served as the terminal electron acceptor, while the carbon skeleton of isethionate functioned as an accessory electron donor for the reduction of sulfite. Cysteate (alanine-3-sulfonate) and sulfoacetaldehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 23 publications
8
103
0
Order By: Relevance
“…Sulphide possibly produced in the reduction of the sulphonate moiety would reduce the bulk phase redox potential. Lie et al [16] reported that a strain of Desulfovibrio utilized some sulphonates as electron acceptor in place of sulphates. Hence it is likely that the dye degradation products such as sulphides might be the cause for the lower ORP in dye containing reactors than the control reactor.…”
Section: Redox Potential Variationmentioning
confidence: 99%
“…Sulphide possibly produced in the reduction of the sulphonate moiety would reduce the bulk phase redox potential. Lie et al [16] reported that a strain of Desulfovibrio utilized some sulphonates as electron acceptor in place of sulphates. Hence it is likely that the dye degradation products such as sulphides might be the cause for the lower ORP in dye containing reactors than the control reactor.…”
Section: Redox Potential Variationmentioning
confidence: 99%
“…Microorganism plays a very important role in the biodegradation and mineralization of these dyes which is of great significance [3,4]. In present study screening for dye decolorization bacteria was performed using various dye contaminated sample.…”
Section: * Corresponding Authormentioning
confidence: 99%
“…We found both the anticipated 250-fold increase in specific activity and enzyme reactions in cell-free extracts Laue et al 1997b). The sulfonate moiety was recovered as sulfide (Lie et al 1996;Laue et al 1997b) or sulfate ) when the sulfonate was supplied as electron acceptor or electron donor, respectively.…”
Section: Introductionmentioning
confidence: 99%